1990
DOI: 10.1128/jb.172.6.3519-3523.1990
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biological ice nuclei from a lichen

Abstract: Biological ice nuclei (active at approximately-40C) were extracted from cells of the lichen Rhizoplaca chrysokuca by sonication. Sensitivity to proteases, guanidine hydrochloride, and urea showed these nuclei to be proteinaceous. The nuclei were relatively heat stable, active from pH 1.5 to 12, and active without lipids, thereby demonstrating significant differences from bacterial ice nuclei.It has recently been discovered that many species of lichens (symbiotic associations of fungi and algae) are capable of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 23 publications
2
67
0
1
Order By: Relevance
“…In order to assess their activity as CCN or IN it is not relevant whether they are alive or not. The important feature is the shape and presence of the active proteins which actually act as nuclei (Kieft and Ruscetti, 1990). Therefore, it is not the viability of the fungal spore that affects its IN activity, but whether the ice nucleation active proteins on its surface are denatured or not.…”
Section: Cfu Vs Total Spore Countmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess their activity as CCN or IN it is not relevant whether they are alive or not. The important feature is the shape and presence of the active proteins which actually act as nuclei (Kieft and Ruscetti, 1990). Therefore, it is not the viability of the fungal spore that affects its IN activity, but whether the ice nucleation active proteins on its surface are denatured or not.…”
Section: Cfu Vs Total Spore Countmentioning
confidence: 99%
“…Lichen were found to nucleate ice at temperatures higher than −8 • C and some even at temperatures higher than −5 • C (Kieft, 1988). The lichen fungus Rhizoplaca chrysoleuca was even found to be an active ice nucleus at temperatures as high as −2 • C (Kieft, 1988;Kieft and Ruscetti, 1990). To date, only a few fungus species have been found to be active ice nucleators: besides the above mentioned lichen these are Fusarium avenaceum and Fusarium acuminatum (Pouleur et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…INPs produced by bacteria and fungi are, however, often unaffected by this temperature. This includes leaf-derived ice nuclei (Schnell and Vali, 1973), most strains of IN M. alpina , IN lichen (Kieft and Ruscetti, 1990), and IN Fusarium spp. (Pouleur et al, 1992), although the onset temperature of activity of cell-free INPs of F. avenaceum was lowered when heated > 40 • C (Hasegawa et al, 1994).…”
Section: Heat Treatmentsmentioning
confidence: 99%
“…Similarly, several ice nucleation experiments were carried out with species of lichens (Ashworth and Kieft, 1992;Kieft, 1988;Kieft and Ahmadjian, 1989;Kieft and Ruscetti, 1990), which are symbiotic organisms wherein fungi and algae and/or cyanobacteria form a single biological entity (Nash, 2008). In one particular study, Rhizoplaca chrysoleuca, a species of lichen, was found to induce freezing at approximately −4 • C (Kieft and Ruscetti, 1990). However, the ice nucleation properties of spores from lichens were not addressed.…”
Section: Is An Increase In the Medianmentioning
confidence: 99%